2016
DOI: 10.1155/2016/2358321
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen: A Marker in Predicting Diabetic Foot Ulcer Severity

Abstract: Aims. To examine whether fibrinogen levels are a valuable biomarker for assessing disease severity and monitoring disease progression in patients with diabetic foot ulcer (DFU). Methods. A retrospective study was designed to examine the utility of fibrinogen in estimating disease severity in patients with DFU admitted to our hospital between January 2015 and January 2016. In total, 152 patients with DFU were enrolled in the study group, and 52 age and gender matched people with diabetes but no DFU were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
6
20
0
Order By: Relevance
“…The first one of these was the study performed by Weigelt et al [ 17 ], and it was shown that there was no significant difference between the patients with and without diabetic ulcer regarding serum fibrinogen levels. The second one of these was the study performed by Li et al [ 19 ], and serum fibrinogen levels were found to be associated with the severity of diabetic foot ulcer and undergoing amputation. In our study, serum fibrinogen levels were found to be effective for discriminating infected diabetic foot ulceration from uninfected diabetic foot ulceration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first one of these was the study performed by Weigelt et al [ 17 ], and it was shown that there was no significant difference between the patients with and without diabetic ulcer regarding serum fibrinogen levels. The second one of these was the study performed by Li et al [ 19 ], and serum fibrinogen levels were found to be associated with the severity of diabetic foot ulcer and undergoing amputation. In our study, serum fibrinogen levels were found to be effective for discriminating infected diabetic foot ulceration from uninfected diabetic foot ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of purulent discharge or two or more findings of inflammation (erythema, local warmth, local tenderness, pain, and induration) in diabetic ulcer were considered to be evidence of infection. Discrimination of IDFU and NIDFU was performed according to Infectious Diseases Society of America guidelines [ 19 ]. The patients followed up with the diagnosis of type 2 diabetes mellitus and who had no diabetic foot ulcer were determined to be the control group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented results indicate that the DHX58 risk variant regulates DHX58, RAB5C, KCNH4, and HSPB9; interestingly, previous global GWAS implicated these four genes in CAD 17 . Furthermore, markers from RAB5C were associated with fibrinogen levels, which are known to be elevated in diabetic patients, especially those with foot ulcers 40 . Our results pointed to significant (p-value < 0.003) interactions between TG and (HOMA-IR and C-peptide levels) and between FPG and HOMA-β at genotypes homozygous for a risk allele.…”
Section: Aif1 Prrc2a Apom Bag6 C6orf47 Csnk2b Gpank1 Ly6g5b Lmentioning
confidence: 97%
“…Plain radiography, positron emission tomography (PET), MRI and leukocyte counting were other OCOMs used for the diagnosis of osteomyelitis. The OCOMs with the highest PPV (96%) and NPV (94%) in this subgroup were MRI and PET, respectively, but they require more time and resources than the probe-to-bone test [33,62]. LR+ and LR− have only been calculated for the probe-to-bone test, which gives more support for its use.…”
Section: Variables and Ocoms For Assessment Of The Characteristics Ofmentioning
confidence: 95%